Nutritional Status and Number of Comorbid in Adult Patients With COVID-19 - Fathiya Andara; Muh Nur Hasan Syah (Poltekkes Kemenkes Palu, 2023)
During the last two years, the death rate due to the COVID-19 pandemic in Indonesia has reached 157,000 people, with comorbid diseases being the most significant factor in the incidence of mortality in COVID-19 patients. Examining the nutritional status and number of comorbidities in COVID-19 patients was the study's main goal. This study is an analytic observational, quantitative study that uses survey research design and cross-sectional approach design. The research samples were taken by a purposive sampling approach, so that all samples that met the inclusion criteria were taken (N= 136) According to the study's findings, there was no linkage among nutritional status and the amount of comorbidities among adults and the elderly. (p value = 0.910 and p = 0.220) and based on gender (p value = 0.937 and p = 0.795). For these reasons, In order to obtain more precise results, there is a need for further research on additional variables that can affect the frequency of comorbidities in COVID-19 patients.